PENGARUH HEDONIC MOTIVATION, DISPLAY PRODUCT, DAN TIME SCARCITY PROMOTION TERHADAP IMPULSIVE BUYING BEHAVIOR DI STARBUCKS SURABAYA - Nathanael, Evan Kevin; Budidharmanto, Lexi Pranata (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the effect of hedonic motivation, product display, and time scarcity promotions on impulsive buying behavior among Starbucks consumers in Surabaya. A quantitative approach was employed, involving 208 purposively selected Gen Z respondents who had previously engaged in impulsive purchases. The multiple linear regression analysis indicates that all three independent variables significantly and positively influence impulsive buying behavior. Among them, time scarcity promotion shows the most dominant effect, followed by product display and hedonic motivation. These findings suggest that emotional and visually driven marketing strategies, combined with temporal urgency, can effectively trigger unplanned consumer purchases. This study offers practical insights for marketers, particularly in the F&B sector, in developing targeted promotional strategies.